Rekindling governments from within: Getting public sector elite officials to support government reform in Brazil - Monica Pinhanez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper shows how an elite cadre of public sector officials played a key role in the success of administrative reforms in Brazil's state tax administration bureaus in the 1990s. The success of the reforms strengthened public sector bureaucracies and institutions at all government levels, predominantly in the tax departments. At the state level, the tax administrative reforms comprised complex changes in organizational structure, technology, and institutional arrangements. These reforms resulted in increased tax revenues, tax compliance, and successful restructuring. For the public officials who took part in the process, the reforms meant finding a new identity, and a new mission. As such, this paper explores an alternative mode of getting public sectors officials to commit and own public sector changes.
Keywords: H2; H11; H71; H83; 330; tax administrative reform; elites; public sector bureaucrats